Reading comprehension in university students, levels achieved and teaching strategies for improvement: A systematic review - Alemán Caballero, Yusmeidy (2025)
The present research aimed to analyze the levels of reading comprehension achieved by university students and the teaching strategies that can enhance this skill. A systematic review was conducted based on the PRISMA method, identifying 48 articles published since 2020. The findings indicate that, although some students manage to reach the literal level, the majority demonstrate a poor command of reading comprehension, particularly in critical and appreciative understanding. Among the most commonly used teaching strategies to improve this indicator are the highlighting technique, identifying main ideas, the SQA methodology (Know, Want to know, Learned), metacognitive summaries, concept maps, and interactive strategies mediated by ICT. In conclusion, it is essential to implement these strategies, as reading comprehension directly impacts students' academic performance and professional development